THE TRUTHS ABOUT THE SOUTH AMERICAN UNION - Miranda, Roberto (2013)
Recently, South America has shown more international presence than in past times. One feature of this phenomenon has been a continual claim related to the concept of integration. In fact, important political decisions and diplomatic actions tending to the building of an integrationist system have being carried out. Clearly, this has raised expectations. However and despite the positive political signs and rhetorical claims, it is also undeniable that different questions have lost momentum and, consequently, have lessened the velocity of the integrationist project.